2007
DOI: 10.4103/0019-5278.32462
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal problems among workers of an Iranian communication company

Abstract: Introduction:Work-related musculoskeletal disorders (WMSDs) are a common health problem throughout the world and a major cause of disability in the workplace. Awkward working posture is a main risk factor for developing WMSDs. Assessment of exposure level to WMSDs risks can be an appropriate base for planning and implementing interventional ergonomics program in the workplace. This study was conducted among workers of an Iranian communication company with the objectives of a) determination of WMSDs prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 26 publications
6
20
0
2
Order By: Relevance
“…The prevalence rates for lower back, knees, neck, shoulders and wrists/hands symptoms were over 55%. This is in agreement with Choobineh, Tabatabaei, Tozihian, et al [20]. Regarding the lower back symptoms, which had the highest rate of prevalence among the assembly workers, it is worth noting that Haynes and Williams pointed out that in jobs with more sedentary activities (such as jobs of assembly workers in the telecommunication industry), there could be a high rate of lower back problems [25].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The prevalence rates for lower back, knees, neck, shoulders and wrists/hands symptoms were over 55%. This is in agreement with Choobineh, Tabatabaei, Tozihian, et al [20]. Regarding the lower back symptoms, which had the highest rate of prevalence among the assembly workers, it is worth noting that Haynes and Williams pointed out that in jobs with more sedentary activities (such as jobs of assembly workers in the telecommunication industry), there could be a high rate of lower back problems [25].…”
Section: Discussionsupporting
confidence: 76%
“…In this industry, awkward posture and repetitive movements are very common [20]. Most job activities are characterized by seated posture with the worker's head and trunk bent forward and the shoulders flexed and abducted, or standing posture outstretched to reach for overhead components.…”
Section: Introductionmentioning
confidence: 99%
“…A research was conducted by Alireza Choobineh et.al. [11] on musculoskeletal problems among workers of an Iranian communication company. They found that there was very high score of RULA (action level 3 & 4).…”
Section: Discussionmentioning
confidence: 99%
“…The entrance manhole was also increased from 800 to 1200mm to improve ease access in and out of the FBHEs especially during emergency operations. The author further recommends external covers to be provided at the Fans to reduce the sound and vibrations which affect the workers during maintenance [22][23][24][25][26][27][28]. The fans should also be installed with silencers to reduce the sound.…”
Section: Improvementsmentioning
confidence: 99%